The Relationship Between Career Maturity and Students Advanced Education Aspiration Level - Emisa Sucika (Jurnal Counseling Care, 2022)
This research is based on the presence of students who are confused about choosing an advanced school to choose, students who do not care about their further education and students who enter secondary school because of trends and requests from parents. The purpose of this study is to describe 1) Career Maturity Descriptions, 2) Advanced Education Aspirations, 3) Relationship between Career Maturity and Further Education Aspirations. This research was conducted using the descriptive correlation method. The study population was 210 students and a sample of 68 students who were selected by simple random sampling technique. The instrument used was a questionnaire. Meanwhile, for data analysis using percentage and correlation techniques. Based on the results of research on the relationship between career maturity and the level of aspirations for further education of students in class IX of Juniour High Schools 1, Guguak District, Limapuluh Kota, the following conclusions can be drawn: 1) The career maturity of students at SMP Negeri 1 Guguak District is in the fairly good category. 2) The aspirations for further education of students at SMP Negeri 1 Guguak District are in the high enough category. 3) The relationship between career maturity and the level of aspirations for further education of students in class IX of SMP Negeri 1, Guguak District, Limapuluh Kota. Based on this research, it is recommended that guidance and counseling teachers be able to increase information about careers for further education so that they can direct the desire of the conscience of students to choose without being burdened.